Rapid degradation of FAD following lysis of Neurospora crassa cells: Consequences for evaluation of flavin composition in vivo. - L. Scheideler; B. Hahne; H. Ninnemann (Fungal Genetics Reports, 1984)
Rapid degradation of FAD following lysis of Neurospora crassa cells: Consequences for evaluation of flavin composition in vivo.